Involvement of NDPK-B in glucose metabolism-mediated endothelial damage via activation of the hexosamine biosynthesis pathway and suppression of O-GlcNAcase activity - Chatterjee, Anupriya; Eshwaran, Rachana; Poschet, Gernot; Lomada, Santosh K.; Halawa, Mahmoud; Wilhelm, Kerstin; Schmidt, Martina; Hammes, Hans-Peter; Wieland, Thomas; Feng, Yuxi (Cells, 2020)
Our previous studies identified that retinal endothelial damage caused by hyperglycemia or nucleoside diphosphate kinase-B (NDPK-B) deficiency is linked to elevation of angiopoietin-2 (Ang-2) and the activation of the hexosamine biosynthesis pathway (HBP). Herein, we investigated how NDPK-B is involved in the HBP in endothelial cells (ECs). The activities of NDPK-B and O-GlcNAcase (OGA) were measured by in vitro assays. Nucleotide metabolism and O-GlcNAcylated proteins were assessed by UPLC-PDA (Ultra-performance liquid chromatography with Photodiode array detection) and immunoblot, respectively. Re-expression of NDPK-B was achieved with recombinant adenoviruses. Our results show that NDPK-B depletion in ECs elevated UDP-GlcNAc levels and reduced NDPK activity, similar to high glucose (HG) treatment. Moreover, the expression and phosphorylation of glutamine:fructose-6-phosphate amidotransferase (GFAT) were induced, whereas OGA activity was suppressed. Furthermore, overall protein O-GlcNAcylation, along with O-GlcNAcylated Ang-2, was increased in NDPK-B depleted ECs. Pharmacological elevation of protein O-GlcNAcylation using Thiamet G (TMG) or OGA siRNA increased Ang-2 levels. However, the nucleoside triphosphate to diphosphate (NTP/NDP) transphosphorylase and histidine kinase activity of NDPK-B were dispensable for protein O-GlcNAcylation. NDPK-B deficiency hence results in the activation of HBP and the suppression of OGA activity, leading to increased protein O-GlcNAcylation and further upregulation of Ang-2. The data indicate a critical role of NDPK-B in endothelial damage via the modulation of the HBP.
Gesehen am 26.11.2020